POTENSI DUSUNG NEGERI HILA KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Ibnu Alwi Heluth; Moda Talaohu; Yulianus Komul (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to determine the potential of dusung and the distribution patterns of dusung plants in Hila Village, Leihitu District, Central Maluku Regency. The method used in this research is a purposive sampling survey method. Vegetation found in the research area consisted of 7 plots with a total area of 98.00 m² or 0.98 ha. There are species that dominate at each level. At the tree level, the dominant species is gandaria with species: Bouea macrophylla and family: Anacardiaceae. At the pole level, the dominant species is clove with species: Syzygium aromaticum and family: Myrtaceae. At the sapling level, the dominant species is nutmeg with species: Myristica fragrans and family: Myristicaceae. Meanwhile, at the seedling level, the dominant species is clove with species: Syzygium aromaticum and family: Myrtaceae. The distribution pattern index shows the magnitude of the distribution pattern index value from each level, namely seedling level of 0.07, pole level of 0.13, sapling level of 0.14, and tree level of 0.11. The distribution pattern of plants at the seedling, sapling, pole, and tree levels falls into the category of clustered distribution pattern.